"I've found it extremely draining": Emotional labour and the lived experience of line managing neurodiversity. Issue 7 (4th November 2019) - Richards, James; Sang, Kate; Marks, Abigail; Gill, Susannah
Abstract : Purpose: The purpose of this paper is to address a significant gap in the line manager, HRM and the diversity management literature, that of exploring the role and significance of emotional labour (EL) in relation to the lived experienced of line managing neurodiversity. Design/methodology/approach: A qualitative approach was used to explore lived experiences of line managers responsible for managing neurodiverse employees. Interviews were conducted with line managers employed in the UK transport industry. Findings: The findings provide rich insights into line managing neurodiversity. A key overall finding is reasonable adjustments deemed essential to support neurodiverse employees require a myriad of hidden, complex, time consuming and often emotionally draining interactions with disabled employees, the employee's wider team, and HRM and occupational health (OH) practitioners. Research limitations/implications: This is an exploratory study and therefore limited by nature of the research design, industry focus, scope of study and sample size. Practical implications: The findings have the potential to inform HRM and OH practitioner support for line managers responsible for managing neurodiverse employees. Social implications: The study contributes to wider societal attempts to make employment more inclusive to a range of historically disadvantaged groups. Originality/value: The study fills an important gap in the HRM literature on line managing neurodiverse employees. The study makes a specific and unique contribution to extensive literatures on line management, disability and EL.